Murder, handcrafted eaudiobook - Alan, Isabella (Amish Quilt Shop Mystery, 2016)
Spring has arrived in Holmes County, and Angie couldn't be happier. She's got great friends, a thriving business, and is in the perfect relationship with Sheriff James Mitchell. The only thing raining on her parade is her mother drafting her into a massive home renovation project—and using their sudden mother/daughter bonding time to comment on Angie's ticking biological clock. The house's repairs and upgrades between the Amish craftsmen and their Englisch counterparts are proceeding well until a tremendous shock comes to the workers when the electrician is found dead on site. With the sheriff suspecting foul play, it falls to Angie to root a killer out of the woodwork . . .